LEVERAGING CONTEMPORARY TECHNOLOGIES TO INCREASE SCIENTIFIC EXPOSURE IN POST-PRIMARY EDUCATION SYSTEM OF EDO STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
In the ever-evolving landscape of education, contemporary technology plays a pivotal role in shaping students’ learning experiences. This study aims to explore how exposure to technology impacts scientific literacy and engagement among secondary school students. A quasi-experimental design was employed, with a treatment group exposed to contemporary technology and a control group receiving traditional instruction. The primary outcome measure was scientific exposure, assessed through pre- and post-tests. A t-test analysis was conducted to compare the treatment and control groups. The treatment group exhibited a significant improvement in scientific exposure compared to the control group (p < 0.05). Students exposed to contemporary technology demonstrated a deeper understanding of scientific concepts. No significant gender differences were observed in the impact of technology exposure on scientific exposure (p > 0.05). Conclusion: Contemporary technology enhances students’ scientific exposure, fostering deeper understanding and engagement. Its benefits are gender-neutral, benefiting both male and female students equally. As educators embrace technology, they must ensure equitable access and leverage its potential to create inclusive learning environments.